Dynamic analysis of offshore wind turbines subjected to the combined wind and ice loads based on the cohesive element method - Wang, Bin; Liu, Yingzhou; Zhang, Jianhua; Shi, Wei; Li, Xin; Li, Ying (Frontiers in Marine Science, 2022)
Ice loads are an important and decisive factor for the safe operation of offshore wind turbines (OWTs). In severe environment load cases, it shall lead to prominent ice-induced vibration and ice-induced fatigue failure of OWT structures. Based on the cohesive element method (CEM) and considering the pile–soil interaction used by nonlinear distributed springs, the full interaction model of the ice and monopile OWT structure with an ice-breaking cone in a cold sea region is established in this study. Furthermore, the Tsai-Wu failure criterion and the empirical failure formula of maximum plastic failure strain are used to describe the mechanical behavior of ice bending failure in the collision simulation tool LS-DYNA, and the dynamic ice loads under different ice velocities and cone angles are statistically analyzed. Finally, according to the interaction process between sea ice and OWT containing the ice-breaking cone, the dynamic response of OWT under the combined wind and ice loads is studied, and the most reasonable ice-breaking cone angle is determined. The results show that the method adopted in this paper can well simulate the bending failure process of sea ice. Concurrently, the cone angle has a significant impact on the dynamic response and damage of the OWT, and the recommended optimal cone angle is 60.